Physical Exercise in Major Depression: Reducing the Mortality Gap While Improving Clinical Outcomes - Belvederi Murri, Martino; Ekkekakis, Panteleimon; Magagnoli, Marco; Zampogna, Domenico; Cattedra, Simone; Capobianco, Laura; Serafini, Gianluca; Calcagno, Pietro; Zanetidou, Stamatula; Amore, Mario (Frontiers in Psychiatry, 2019)
Major depression shortens life while the effectiveness of frontline treatments remains modest. Exercise has been shown to be effective both in reducing mortality and in treating symptoms of major depression, but it is still underutilized in clinical practice, possibly due to prevalent misperceptions. For instance, a common misperception is that exercise is beneficial for depression mostly because of its positive effects on the body (“from the neck down”), whereas its effectiveness in treating core features of depression (“from the neck up”) is underappreciated. Other long-held misperceptions are that patients suffering from depression will not engage in exercise even if physicians prescribe it, and that only vigorous exercise is effective. Lastly, a false assumption is that exercise may be more harmful than beneficial in old age, and therefore should only be recommended to younger patients. This narrative review summarizes relevant literature to address the aforementioned misperceptions and to provide practical recommendations for prescribing exercise to individuals with major depression.